High-sealing-performance flame-retardant composite film and preparation method thereof
By setting a multi-layer structure in the composite film, the flame retardant efficiency and surface density are improved by combining phosphorus-nitrogen synergistic flame-retardant PET with nano-silica. Combined with the intermediate layer of modified aluminum hydroxide and zinc borate and the inner sealing layer of ethylene-vinyl acetate copolymer, the problem of incompatibility between flame retardant and sealing performance in the prior art is solved, and high sealing performance and excellent flame retardant performance are achieved.
Patent Information
- Application Number
- CN202511241837.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-02
- Publication Date
- 2025-11-28
AI Technical Summary
Existing phosphorus-nitrogen synergistic flame retardants and intumescent flame retardants cannot simultaneously improve flame retardancy and sealing performance, resulting in high water vapor permeability, which cannot meet the requirements of high-precision sealing. Furthermore, multilayer composite films are prone to delamination under long-term humid and hot environments, and have weak interfacial bonding.
By setting up an outer layer, an intermediate layer, a transition layer, and an inner sealing layer in sequence, the flame retardant efficiency and surface density of the outer layer are improved by using phosphorus-nitrogen synergistic flame retardant PET and nano-silica composite. Polypropylene is used as the matrix to load modified aluminum hydroxide and zinc borate to form an intermediate layer synergistic flame retardant system. Ethylene-vinyl acetate copolymer and maleic anhydride grafted polyethylene are blended to form an inner sealing layer. An epoxy resin and nano-silicon carbide transition layer is set in the intermediate layer and the inner sealing layer to improve the interfacial bonding force.
It achieves high sealing performance and excellent flame retardant properties, with a limiting oxygen index of 39%, a UL-94 rating of V-0, a water vapor transmission rate of 8.5 g/m2·day, and an oxygen transmission rate of 10±1 cm3/m2·day, thereby improving the interfacial bonding strength and resistance to electrolyte corrosion of the material.
Smart Images

Figure CN121019083A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite membrane material preparation technology, specifically to a high-sealing flame-retardant composite membrane and its preparation method. Background Technology
[0002] Flame-retardant composite films have wide applications in new energy battery packaging, building fire protection, and electronic equipment protection, with halogenated (bromine-based and chlorine-based) flame retardants being the most commonly used. Halogenated flame retardants primarily interrupt the combustion chain reaction by capturing free radicals, exhibiting high flame-retardant efficiency and low cost. However, these flame retardants release highly toxic gases such as dioxins and hydrogen halides during combustion, posing serious environmental safety problems. Existing technologies have developed phosphorus-nitrogen synergistic flame retardants and intumescent flame retardants. These two types of flame retardants primarily employ a dual mechanism of gas-phase flame retardancy and condensed-phase char formation, offering better environmental and operational safety.
[0003] Chinese Patent Publication No. CN119874779A discloses a method for preparing a phenolic acid-based phosphorus-nitrogen flame retardant, the flame retardant itself, and its applications. Using natural and renewable phenolic acid compounds as the main raw material, the method involves an addition reaction between the active PH bond in the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide structure and the carbon-carbon double bond in the phenolic acid compound, and a nucleophilic substitution reaction between the P-Cl group in the hexachlorocyclotriphosphazene structure and the phenolic hydroxyl and carboxyl groups in the phenolic acid compound. This process yields a phenolic acid-based phosphorus-nitrogen flame retardant exhibiting both gas-phase and condensed-phase flame-retardant mechanisms. This flame retardant contains phosphorus elements in different valence states, allowing it to simultaneously exert both condensed-phase and gas-phase flame-retardant mechanisms, resulting in high flame-retardant efficiency and good compatibility with polylactic acid.
[0004] Chinese Patent Publication No. CN116674238A discloses a composite membrane with multiple flame-retardant spaces, its preparation, and its application. It uses benzonitrile and dicyandiamide to prepare benzoic acid melamine as a gas source, and lignin-grafted phenylphosphoyl dichloride as a carbon and acid source. These two are compounded to form an intumescent flame retardant, which is then used to prepare a flame-retardant TPU film. Simultaneously, a phosphorus-nitrogen-doped quantum dot solution is prepared using glucose as a carbon source, phytic acid as a phosphorus source, and triethylamine as a nitrogen source. This solution is then used to impregnate polyester fibers to produce flame-retardant polyester fibers. The resulting flame-retardant TPU film and flame-retardant polyester fibers are then hot-pressed and cold-pressed to form the composite membrane with multiple flame-retardant spaces. This composite membrane exhibits excellent flame-retardant properties and can be used to manufacture inflatable boats.
[0005] However, existing phosphorus-nitrogen synergistic flame retardants and intumescent flame retardants often fail to simultaneously improve flame retardancy and sealing performance. This is because achieving high flame retardancy with phosphorus-nitrogen synergistic flame retardants often requires an addition amount greater than or equal to 25 wt%. This high addition amount disrupts the continuity of the matrix, leading to the formation of micropores within the membrane and a sharp increase in water vapor permeability. Furthermore, the polar groups of the flame retardant have poor compatibility with non-polar substrates (such as PP), easily causing delamination through interfacial enrichment. Achieving high flame retardancy with intumescent flame retardants requires porous charring to isolate oxygen, while sealing requires a dense, defect-free membrane; the physical mechanisms of these two are contradictory. In addition, the processing temperature of the flame retardant is close to its decomposition point (e.g., ammonium polyphosphate at 250℃), causing pre-decomposition and bubble generation, further reducing sealing performance and resulting in high water vapor or electrolyte permeability (>30 g / m³). 2 The 24-hour sealing time is insufficient to meet the high-precision sealing requirements of lithium battery packaging. Furthermore, multilayer flame-retardant composite films are prone to problems such as weak interfacial bonding (peel strength <10N / cm) and delamination under long-term humid and hot environments due to differences in material polarity. This makes it difficult to simultaneously meet the multi-functional requirements of flame retardancy, sealing, and weather resistance, thus limiting their application in complex environments.
[0006] In view of this, it is necessary to design a high-sealing flame-retardant composite membrane and its preparation method to solve the above problems. Summary of the Invention
[0007] In view of the technical problems existing in the background art, this application provides a high-sealing flame-retardant composite film and its preparation method. A high-sealing flame-retardant composite film is obtained by sequentially stacking an outer layer, an intermediate layer, a transition layer, and an inner sealing layer. The flame-retardant efficiency and surface density of the outer layer are improved by combining phosphorus-nitrogen synergistic flame-retardant PET with nano-silica. Modified aluminum hydroxide and zinc borate are loaded onto polypropylene as the matrix to form a synergistic flame-retardant system in the intermediate layer. The inner sealing layer is formed by blending ethylene-vinyl acetate copolymer with maleic anhydride-grafted polyethylene. Furthermore, this application further improves the flame-retardant and sealing performance by setting a transition layer composed of epoxy resin and nano-silicon carbide between the intermediate layer and the inner sealing layer, while also enhancing the interfacial bonding between the materials. This application overcomes the technical barrier of incompatibility between flame retardancy and sealing performance through synergistic innovation of materials, structure, and process, providing a high-safety, long-life packaging solution for new energy vehicle batteries, high-end electronic devices, etc.
[0008] In a first aspect, embodiments of this application provide a high-sealing flame-retardant composite film, comprising an outer layer, an intermediate layer, a transition layer, and an inner sealing layer stacked sequentially. The outer layer material comprises flame-retardant PET and nano-silica; the intermediate layer material comprises a polypropylene matrix, modified aluminum hydroxide, and zinc borate; the transition layer material comprises epoxy resin and nano-silicon carbide; and the inner sealing layer material comprises ethylene-vinyl acetate copolymer and maleic anhydride-grafted polyethylene. The flame-retardant PET also contains 12-20 wt% phosphorus-nitrogen synergistic flame retardant. The outer layer and the intermediate layer are bonded by physical entanglement, and the transition layer and the inner sealing layer are bonded by chemical cross-linking.
[0009] Furthermore, the thickness of the highly sealing flame-retardant composite film is 180-250 μm.
[0010] Furthermore, in the high-sealing flame-retardant composite film, the outer layer has a thickness of 40-60 μm, the middle layer has a thickness of 70-90 μm, the transition layer has a thickness of 5-10 μm, and the inner sealing layer has a thickness of 50-90 μm.
[0011] Furthermore, the mass percentage of nano-silica in the outer layer material is 3-5 wt%; the mass percentage of modified aluminum hydroxide and zinc borate in the middle layer material is 25-35 wt%; in the transition layer, the mass ratio of epoxy resin to nano-silicon carbide is (9-11):1; in the inner sealing layer, the mass ratio of ethylene-vinyl acetate copolymer to maleic anhydride grafted polyethylene is 80:(15-25).
[0012] Furthermore, the mass ratio of modified aluminum hydroxide to zinc borate is (15-25):10.
[0013] Furthermore, the ethylene-vinyl acetate copolymer contains 25-30% vinyl acetate.
[0014] Furthermore, the inner sealing layer material also contains 0.01-10 wt% graphene.
[0015] Secondly, embodiments of this application provide a method for preparing a highly sealing flame-retardant composite film, comprising the following steps: S1, Flame-retardant PET granules are mixed with nano-silica and melt-granulated to obtain an outer layer material; polypropylene matrix is mixed with modified aluminum hydroxide and zinc borate and melt-granulated to obtain an intermediate layer material; then, the outer layer material and the intermediate layer material are melted separately and extruded together, and after cooling, a first composite film is obtained in which the intermediate layer is closely attached to the outer layer and the thickness of the intermediate layer is greater than the thickness of the outer layer. S2, epoxy resin and nano silicon carbide are uniformly mixed, diluted with acetone and ultrasonically dispersed to obtain a uniform spraying liquid. Then, the spraying liquid is uniformly sprayed onto the surface of the intermediate layer of the first composite film prepared in step S1, and left to stand for the solvent to evaporate naturally to obtain a second composite film containing a transition layer. S3, after mixing and melting ethylene-vinyl acetate copolymer with maleic anhydride grafted polyethylene, the mixture is extruded and coated onto the transition layer surface of the second composite film prepared in step S2, and then hot-pressed to obtain a third composite film containing an inner sealing layer. S4. The third composite film prepared in step S3 is subjected to fluorocarbon plasma surface treatment. Then, the treated composite film roll is transferred to a constant temperature drying room for static curing. Finally, it is rolled up to obtain a high-sealing flame-retardant composite film.
[0016] Further, in step S1, the melt granulation process of the outer layer material is as follows: first, flame-retardant PET granules are premixed with nano-silica, then melt granulated at 240-250℃ using a twin-screw extruder, and finally dried; in step S1, the melt granulation process of the intermediate layer material is as follows: first, polypropylene matrix is premixed with modified aluminum hydroxide and zinc borate, then melt granulated at 220-230℃ using a twin-screw extruder, and finally dried; the co-extrusion mentioned in step S1 specifically refers to the simultaneous extrusion of the outer layer material and the intermediate layer material through a co-extrusion die, followed by rapid shaping through a cooling roller; in step S2, the solid content in the spraying liquid is 15-25%, and the spraying amount is set to 4-8 g / m³. 2 In step S3, the melting temperature of the ethylene-vinyl acetate copolymer and maleic anhydride-grafted polyethylene is 170-180℃; in step S3, a two-roller hot press is used for hot pressing, wherein the upper roller temperature is set to 160-165℃, the lower roller temperature is set to 150-155℃, the pressure is set to 15-20MPa, and the hot pressing time is 20-40s; in step S4, the fluorocarbon plasma surface treatment specifically involves using an atmospheric pressure plasma treatment device to treat the outer surface of the third composite film in a mixed atmosphere of hexafluoropropylene and argon, and the treatment time is 30-40s; in step S4, the temperature of the constant temperature drying oven is 35-45℃, and the static curing time is 24-30h.
[0017] Furthermore, in the mixed atmosphere of hexafluoropropylene and argon, the volume ratio of hexafluoropropylene to argon is 1:5.
[0018] The beneficial effects of this application are as follows: This application provides a high-sealing flame-retardant composite film and its preparation method. The high-sealing flame-retardant composite film is obtained by sequentially stacking an outer layer, an intermediate layer, a transition layer, and an inner sealing layer. The flame-retardant efficiency and surface density of the outer layer are improved by combining phosphorus-nitrogen synergistic flame-retardant PET with nano-silica. A synergistic flame-retardant system for the intermediate layer is formed by loading modified aluminum hydroxide and zinc borate onto polypropylene as the matrix. The inner sealing layer is formed by blending ethylene-vinyl acetate copolymer with maleic anhydride-grafted polyethylene. Furthermore, this application further enhances the flame-retardant and sealing properties by incorporating a transition layer composed of epoxy resin and nano-silicon carbide between the intermediate layer and the inner sealing layer, while also improving the interfacial bonding between the materials.
[0019] (1) In this application, the outer layer material and the middle layer material are melt co-extruded to obtain the first composite film. In the outer layer material, the phosphorus-nitrogen synergistic flame retardant can be dehydrated by thermal decomposition to form a dense carbon layer, which isolates heat and oxygen. Meanwhile, nano-SiO2 fills the gaps between PET molecules, which is beneficial to enhance the density. In the middle layer material, modified ATH and ZnB form a synergistic flame retardant system. Modified ATH decomposes and absorbs heat to reduce the system temperature. ZnB reacts with ATH to generate glassy aluminum borate to cover the substrate and cut off the combustion chain.
[0020] (2) In this application, after coating the inner sealing layer material onto the transition layer surface of the second composite membrane, hot pressing is performed to cause the epoxy resin to undergo a ring-opening reaction with the PP matrix and the maleic anhydride groups on PE-g-MAH to generate COC ether bonds and ester bonds, forming an epoxy network. At the same time, SiC nanoparticles are embedded in the aforementioned covalently bonded epoxy network to achieve mechanical interlocking. In this way, the inner sealing layer and the intermediate layer form a strong bond, effectively improving the sealing performance and electrolyte corrosion resistance of the composite membrane. In addition, the vinyl acetate (VA) groups in EVA can form a hydrogen bond network, extending the gas diffusion path, while the polar grafted chains of PE-g-MAH further reduce oxygen permeability by filling the amorphous region of EVA. The anhydride groups of PE-g-MAH can also form coordination bonds with the metal oxides (such as Al2O3) of the battery casing, improving the heat sealing strength of the composite membrane.
[0021] (3) The outer surface of the high-sealing flame-retardant composite film is also subjected to fluorocarbon plasma surface treatment, which generates a fluorocarbon polymer coating on the PET surface, significantly enhancing hydrophobicity and anti-pollution ability, effectively blocking external water vapor penetration while extending the service life of the composite film in a humid and hot environment.
[0022] (4) In the high-sealing flame-retardant composite membrane provided in this application, firstly, the outer layer of nano-SiO2 fills the gaps between molecules and the middle layer is ceramicized at high temperature to form a sub-nano barrier, thereby blocking permeation through physical means; secondly, chemical cross-linking eliminates interfacial gaps and significantly reduces the permeation channels; thirdly, the PE-g-MAH and graphene layers of the inner sealing layer further enhance the sealing performance, and fluorocarbon surface treatment blocks adsorption permeation on the surface of the composite membrane; through the synergistic effect of four mechanisms—chemical flame retardancy, physical shielding, interfacial bonding, and functional compensation—the composite membrane has excellent flame retardant and sealing performance, with a limiting oxygen index of 39%, a UL-94 rating of V-0, and a water vapor permeability of 8.5 g / m³. 2 • Day, oxygen permeability reaches 10±1cm 3 / m 2 This application overcomes the technical barrier of incompatibility between flame retardancy and sealing performance through synergistic innovation of materials, structure, and process, providing a high-safety, long-life packaging solution for new energy vehicle batteries, high-end electronic devices, and other applications.
[0023] The above description is only an overview of the technical solution of this application. In order to better understand the technical means of this application and to implement it in accordance with the contents of the specification, and to make the above and other objects, features and advantages of this application more obvious and understandable, the following are specific embodiments of this application. Attached Figure Description
[0024] To more clearly illustrate the technical solutions of this application, the accompanying drawings used in this application will be briefly described below. Obviously, the drawings described below are merely some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without any creative effort.
[0025] Figure 1 This is a schematic diagram of the structure of the high-sealing flame-retardant composite membrane in the embodiments of this application; Detailed Implementation The embodiments of the technical solution of this application will now be described in detail with reference to the accompanying drawings. These embodiments are only used to more clearly illustrate the technical solution of this application and are therefore merely examples, and should not be used to limit the scope of protection of this application.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the application; the terms “comprising” and “having”, and any variations thereof, in the specification, claims, and foregoing description of the drawings are intended to cover non-exclusive inclusion.
[0027] In the description of the embodiments of this application, technical terms such as "first" and "second" are used only to distinguish different objects and should not be construed as indicating or implying relative importance or implicitly specifying the number, specific order, or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, "multiple" means two or more, unless otherwise explicitly defined.
[0028] In this document, the term "embodiment" means that a particular feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The appearance of this phrase in various places throughout the specification does not necessarily refer to the same embodiment, nor is it a separate or alternative embodiment mutually exclusive with other embodiments. It will be explicitly and implicitly understood by those skilled in the art that the embodiments described herein can be combined with other embodiments.
[0029] In the description of the embodiments of this application, the term "and / or" is merely a description of the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. Additionally, the character " / " in this document generally indicates that the preceding and following related objects have an "or" relationship. Those skilled in the art can understand the specific meaning of the above terms in the embodiments of this application according to the specific circumstances.
[0030] Existing phosphorus-nitrogen synergistic flame retardants and intumescent flame retardants often fail to simultaneously improve flame retardant and sealing performance, resulting in high water vapor or electrolyte permeability (>30g / m³). 2 The 24-hour sealing time is insufficient to meet the high-precision sealing requirements of lithium battery packaging. Furthermore, multilayer flame-retardant composite films are prone to problems such as weak interfacial bonding (peel strength <10N / cm) and delamination under long-term humid and hot environments due to differences in material polarity. This makes it difficult to simultaneously meet the multi-functional requirements of flame retardancy, sealing, and weather resistance, thus limiting their application in complex environments.
[0031] To address the aforementioned technical problems, this application provides a high-sealing flame-retardant composite film and its preparation method. The outer layer's flame-retardant efficiency and surface density are improved by combining phosphorus-nitrogen synergistic flame-retardant PET with nano-silica. A synergistic flame-retardant intermediate layer is formed by loading modified aluminum hydroxide and zinc borate onto a polypropylene matrix. An inner sealing layer is formed by blending ethylene-vinyl acetate copolymer with maleic anhydride-grafted polyethylene. Furthermore, this application further enhances the flame-retardant and sealing properties by incorporating a transition layer composed of epoxy resin and nano-silicon carbide between the intermediate layer and the inner sealing layer, while also improving the interfacial bonding between the materials.
[0032] Please refer to Figure 1In a first aspect, embodiments of this application provide a highly sealing flame-retardant composite film, comprising an outer layer, an intermediate layer, a transition layer, and an inner sealing layer stacked sequentially. The outer layer material includes flame-retardant PET and nano-silica (SiO2), the intermediate layer material includes a polypropylene (PP) matrix, modified aluminum hydroxide (ATH), and zinc borate (ZnB), the transition layer material includes epoxy resin (EP) and nano-silicon carbide (SiC), and the inner sealing layer material includes ethylene-vinyl acetate copolymer (EVA) and maleic anhydride grafted polyethylene (PE-g-MAH).
[0033] In this embodiment, the outer layer and the middle layer are bonded by physical entanglement, while the transition layer and the inner sealing layer are bonded by chemical cross-linking. Specifically, the chemical cross-linking involves a ring-opening reaction between the epoxy resin and the PP matrix, as well as the maleic anhydride groups on PE-g-MAH, to generate COC ether bonds and ester bonds, forming an epoxy network. Simultaneously, SiC nanoparticles are embedded in the aforementioned covalently bonded epoxy network to achieve mechanical interlocking. This results in a strong bond between the inner sealing layer and the middle layer, effectively improving the sealing performance and electrolyte corrosion resistance of the composite membrane. Furthermore, the vinyl acetate (VA) groups in EVA can form a hydrogen bond network, extending the gas diffusion path, while the polar graft chains of PE-g-MAH further reduce oxygen permeability by filling the amorphous regions of EVA. The anhydride groups of PE-g-MAH can also form coordination bonds with the metal oxides (such as Al2O3) of the battery casing, enhancing the heat-sealing strength of the composite membrane.
[0034] In this embodiment, the thickness of the high-sealing flame-retardant composite film is 180-250 μm, wherein the thickness of the outer layer is 40-60 μm, the thickness of the middle layer is 70-90 μm, the thickness of the transition layer is 5-10 μm, and the thickness of the inner sealing layer is 50-90 μm.
[0035] In this embodiment, the mass percentage of nano-SiO2 in the outer layer material is 3-5 wt%. The mass percentage of modified ATH and ZnB in the intermediate layer material is 25-35 wt%, wherein the mass ratio of modified ATH to ZnB is (15-25):10. Modified ATH and ZnB form a synergistic flame-retardant system, wherein modified ATH decomposes and absorbs heat to lower the system temperature, and ZnB reacts with ATH to generate glassy aluminum borate to cover the substrate and break the combustion chain. In the transition layer, the mass ratio of EP to nano-SiC is (9-11):1. In the inner sealing layer, the mass ratio of EVA to PE-g-MAH is 80:(15-25).
[0036] In the embodiments of this application, the flame-retardant PET contains 12-20wt% phosphorus-nitrogen synergistic flame retardant, and the EVA contains 25-30% vinyl acetate (VA).
[0037] In this embodiment, the inner sealing layer material also contains 0.01-10 wt% graphene.
[0038] The high-sealing flame-retardant composite membrane provided in this application employs three key mechanisms: First, an outer layer of nano-SiO2 fills the molecular gaps, and a middle layer is ceramicized at high temperature to form a sub-nano barrier, physically blocking permeation. Second, chemical cross-linking eliminates interfacial gaps, significantly reducing permeation channels. Third, the inner sealing layer's PE-g-MAH and graphene layers further enhance sealing performance, and fluorocarbon surface treatment blocks adsorption permeation on the composite membrane surface. Through the synergistic effect of four mechanisms—chemical flame retardancy, physical shielding, interfacial bonding, and functional compensation—this composite membrane exhibits excellent flame-retardant and sealing performance, achieving a limiting oxygen index of 39%, a UL-94 rating of V-0, and a water vapor transmission rate of 8.5 g / m³. 2 • Day, oxygen permeability reaches 10±1cm 3 / m 2 ·day.
[0039] Secondly, embodiments of this application provide a method for preparing the high-sealing flame-retardant composite film of the aforementioned scheme, comprising the following steps: S1. Flame-retardant PET granules are mixed with nano-SiO2 and melt-granulated to obtain the outer layer material. PP matrix is mixed with modified ATH and ZnB and melt-granulated to obtain the intermediate layer material. Then, the outer layer material and the intermediate layer material are melted separately and co-extruded. After cooling, a first composite film is obtained where the intermediate layer is tightly attached to the outer layer, and the thickness of the intermediate layer is greater than that of the outer layer.
[0040] In this embodiment, the flame-retardant PET contains 12-20 wt% phosphorus-nitrogen synergistic flame retardant. In the outer layer material, the phosphorus-nitrogen synergistic flame retardant decomposes upon heating and dehydrates to form a dense carbon layer, which isolates heat and oxygen, while nano-SiO2 fills the gaps between PET molecules, which helps to enhance density.
[0041] In this embodiment, the melt granulation process of the outer layer material involves first premixing flame-retardant PET granules with nano-SiO2, then melt granulating them at 240-250°C using a twin-screw extruder, and finally drying. The nano-SiO2 accounts for 3-5 wt% of the outer layer material; an appropriate amount of nano-SiO2 can fill the gaps between PET molecules, enhancing the density of the composite film.
[0042] In this embodiment, the melt granulation process of the interlayer material is as follows: first, the PP matrix is premixed with modified ATH and ZnB, then melt granulated at 220-230℃ using a twin-screw extruder, and finally dried. The modified ATH and ZnB constitute 25-35 wt% of the interlayer material, and the mass ratio of modified ATH to ZnB is (15-25):10.
[0043] In this embodiment, the co-extrusion of the outer layer material and the intermediate layer material after separate melting specifically refers to the simultaneous extrusion of the outer layer material and the intermediate layer material through a co-extrusion die, followed by rapid shaping via a cooling roller. The preferred melting temperature of the outer layer material is 245°C, the preferred melting temperature of the intermediate layer material is 230°C, and the preferred temperature of the cooling roller is 20-25°C. During the simultaneous extrusion process, the contact surfaces of the outer layer material and the intermediate layer material undergo physical entanglement in a high-temperature molten state, achieving initial interlayer bonding.
[0044] S2, EP and nano SiC are uniformly mixed, diluted with acetone and ultrasonically dispersed to obtain a uniform spraying liquid. The spraying liquid is then uniformly sprayed onto the surface of the intermediate layer of the first composite film prepared in step S1. The mixture is left to stand for the solvent to evaporate naturally to obtain a second composite film containing a transition layer.
[0045] In this embodiment, EP and nano-SiC are mixed at a mass ratio of (9-11):1, and the solid content in the spraying liquid is 15-25%. EP is preferably EP828.
[0046] In this embodiment, the spraying amount is set to 4-8 g / m². 2 .
[0047] S3, EVA and PE-g-MAH are mixed and melted, then extruded and coated onto the transition layer surface of the second composite film prepared in step S2, and then hot-pressed to obtain a third composite film containing an inner sealing layer.
[0048] In this embodiment, the melting temperature of EVA and PE-g-MAH is 170-180℃. g The mass ratio of MAH is 80:(15-25).
[0049] In this embodiment, the VA content in EVA is 25-30%.
[0050] In this embodiment, a double-roller hot press is used for hot pressing. The temperature of the upper roller is set to 160-165℃, the temperature of the lower roller is set to 150-155℃, the pressure is set to 15-20MPa, and the hot pressing time is 20-40s.
[0051] S4. The third composite film prepared in step S3 is subjected to fluorocarbon plasma surface treatment. Then, the treated composite film roll is transferred to a constant temperature drying room for static curing. Finally, it is rolled up to obtain a high-sealing flame-retardant composite film.
[0052] In this embodiment, the fluorocarbon plasma surface treatment specifically involves using an atmospheric pressure plasma treatment device to treat the outer surface of the third composite film in a mixed atmosphere of hexafluoropropylene (C3F6) and argon, with a treatment time of 30-40 seconds. The preferred volume ratio of C3F6 to argon is 1:5, the preferred power of the plasma surface treatment is 2kW, and the preferred moving speed is 0.5m / min.
[0053] Fluorocarbon plasma surface treatment can generate a fluorocarbon polymer coating on the PET surface, which significantly enhances hydrophobicity and anti-fouling ability, effectively blocking external water vapor penetration while extending the service life of the composite film in humid and hot environments.
[0054] In this embodiment, the temperature of the constant temperature drying room is 35-45℃, and the curing time is 24-30h.
[0055] The following are some specific embodiments. It should be noted that the embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they shall be performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.
[0056] Example 1 Example 1 provides a method for preparing a high-sealing flame-retardant composite film, comprising the following steps: S1. PET granules containing 15wt% phosphorus-nitrogen synergistic flame retardant and nano-SiO2 are premixed in a high-speed mixer for 10 minutes at a mass ratio of 97:3. Then, the mixture is melt-granulated at 240-250℃ using a twin-screw extruder to obtain the outer layer material. PP matrix, modified ATH, and ZnB are premixed in a high-speed mixer for 15 minutes (1000 rpm) at a mass ratio of 70:20:10. Then, the mixture is melt-granulated at 220-230℃ using a twin-screw extruder to obtain the intermediate layer material. Next, the outer layer material (PET / SiO2) and the intermediate layer material (PP / ATH / ZnB) are fed into a co-extrusion system. The extrusion temperature of the outer layer material is set to 245℃, and the extrusion temperature of the intermediate layer material is set to 230℃. The outer layer material and the intermediate layer material are simultaneously extruded through a co-extrusion die. After rapid cooling and shaping by a 25℃ cooling roller, a first composite film is obtained where the intermediate layer is tightly attached to the outer layer, and the thickness of the intermediate layer is greater than that of the outer layer. The outer layer has a thickness of 40 μm, and the middle layer has a thickness of 80 μm.
[0057] S2, EP828 and nano-SiC are uniformly mixed at a mass ratio of 9:1, diluted with acetone to a solid content of 20%, and ultrasonically dispersed for 30 minutes to obtain a uniform spraying liquid. Then, the spraying liquid is uniformly sprayed onto the surface of the intermediate layer of the first composite film using a high-pressure airless sprayer (nozzle diameter 0.3 mm, pressure 0.5 MPa, spraying amount 5 g / m). 2 The solvent was allowed to evaporate naturally for 5 minutes, resulting in a second composite membrane containing a transition layer. The thickness of the transition layer was approximately 6 μm.
[0058] S3, EVA (containing 28% VA) and PE-g-MAH are mixed at a mass ratio of 80:20 and melted at 180°C using a single-screw extruder. The mixture is then coated onto the transition layer surface of the second composite film using a slot coater. Next, a two-roll hot press is used, with the upper roll set to 160°C and the lower roll to 150°C, at a pressure of 18 MPa for 30 seconds, to obtain a third composite film containing an inner sealing layer. The thickness of the inner sealing layer is 50 μm.
[0059] S4. The third composite membrane prepared in step S3 is subjected to fluorocarbon plasma surface treatment. Specifically, atmospheric pressure plasma treatment equipment is used to treat the outer surface of the third composite membrane for 30 seconds in a mixed atmosphere of hexafluoropropylene (C3F6) and argon (Ar) (C3F6 to Ar volume ratio of 1:5), at a power of 2kW and a moving speed of 0.5m / min. Then, the treated composite membrane roll is transferred to a constant temperature drying oven at 40℃ and allowed to cure for 24 hours. Finally, it is wound up using a constant tension winding machine at a tension of 20N and a speed of 5m / min to obtain a high-sealing flame-retardant composite membrane.
[0060] The contact angle of the outer layer of the high-sealing flame-retardant composite film prepared in Example 1 is ≥115°.
[0061] Example 2 The difference between Example 2 and Example 1 is that the content of phosphorus-nitrogen synergistic flame retardant in the flame-retardant PET is 18wt% (step S1); the mass ratio of PP matrix to modified ATH and ZnB in the intermediate layer material is 65:25:10 (step S2); and the pressure used for hot pressing in step S3 is 20MPa (step S3). Everything else is the same as in Example 1 and will not be repeated here.
[0062] Example 3 The difference between Example 3 and Example 1 is that the content of phosphorus-nitrogen synergistic flame retardant in the flame-retardant PET is 12wt% (step S1); 5wt% graphene is added to the inner sealing layer, i.e., in step S3, EVA (containing 28% VA) is mixed with PE-g-MAH and graphene at a mass ratio of 75:20:5; and the extrusion temperature in step S3 is changed to 170℃. Everything else is the same as in Example 1 and will not be repeated here. Adding an appropriate amount of graphene helps to enhance the sealing performance of the composite film, lowering the extrusion temperature is beneficial for lightweight design, and improves product flowability during processing.
[0063] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no transition layer is provided (no chemical cross-linking is performed), that is, step S2 is omitted, and the inner sealing layer is directly coated onto the surface of the intermediate layer. Everything else is the same as in Example 1, and will not be repeated here.
[0064] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the phosphorus-nitrogen synergistic flame-retardant PET is replaced with a bromine-based flame-retardant PET (a traditional halogen-containing flame-retardant system), no transition layer is provided, and no fluorocarbon surface treatment is performed. The outer layer, middle layer, and inner sealing layer are composited by three-layer co-extrusion. Everything else is the same as in Example 1, and will not be repeated here.
[0065] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that no fluorocarbon surface treatment is performed; after obtaining the third composite film containing the inner sealing layer, conventional cooling and winding are sufficient. Everything else is the same as in Example 1 and will not be repeated here.
[0066] The flame retardant properties of the flame-retardant composite films prepared in Examples 1-3 and Comparative Examples 1-3 were tested: (1) Cut the test sample into 0.1mm×10mm×100mm size, test the limiting oxygen index (LOI) of the flame-retardant composite film according to standard GB / T2406.2-2009, and record the combustion phenomenon; (2) Cut the test sample to a size of 0.1mm×12mm×120mm, test the vertical heat of combustion of the flame-retardant composite film according to standard GB / T2408-2021 (UL-94), record the combustion phenomenon and evaluate the flammability rating.
[0067] The test results for flame retardant performance are shown in Table 1.
[0068] Table 1. Flame retardant properties of the flame retardant composite films prepared in Examples 1-3 and Comparative Examples 1-3 The comparison shows that Examples 1-2 and Comparative Example 3 have relatively higher limiting oxygen indices and higher UL-94 ratings, indicating better flame retardant performance. The relatively poor flame retardant performance of Example 3 is due to the relatively low addition amount of the phosphorus-nitrogen synergistic flame retardant (12wt%). The poor flame retardant performance of Comparative Example 1 is due to the lack of a transition layer in the composite film, leading to interfacial delamination. The flame retardant (ATH / ZnB) agglomerates at the interface, forming a weak boundary layer. Simultaneously, the mismatch in thermal expansion coefficients between the PP matrix and ATH induces microcracks. During combustion, the flame penetrates along these cracks, and the microcracks accelerate oxygen diffusion, preventing the flame retardant from effectively charring. Comparative Example 2 exhibits better flame retardant performance than Comparative Example 1 because the bromine-based flame retardant decomposes and releases HBr free radicals, rapidly capturing active free radicals (such as H· and OH·) in the combustion chain reaction, which is beneficial for efficiently interrupting combustion.
[0069] The sealing performance of the flame-retardant composite films prepared in Examples 1-3 and Comparative Examples 1-3 was tested: (1) The water vapor transmission rate of the flame-retardant composite membrane was tested according to the standard ASTM F-1249, where the test area was 6 cm². 2 The relative humidity is 90%. (2) The oxygen permeability of the flame-retardant composite membrane was tested according to standard ASTM D3985, where the test area was 6 cm². 2 The relative humidity is 0%.
[0070] (3) The peel strength of the flame-retardant composite film before and after aging was tested according to standard GB / T2791-2023. The composite film sample was cut into 25mm×200mm sizes, and 50mm was pre-peeled from one end of the sample as a clamping end. The peeling angle was 180° and the constant speed was 50mm / min. The peel force curve was recorded in real time, and the average value was taken after three repeated measurements. The aging method was to place the flame-retardant composite film in an environment with a temperature of 80℃ and a relative humidity of 90% for 168h.
[0071] The test results for breathability are shown in Table 2.
[0072] Table 2. Sealing performance of the flame-retardant composite films prepared in Examples 1-3 and Comparative Examples 1-3 As can be seen, the water vapor and oxygen permeability of Comparative Example 3 are much lower than those of Comparative Examples 1-2, and the water vapor and oxygen permeability of Examples 1-3 are also much lower than those of Comparative Examples 1-3. That is, the high-sealing flame-retardant composite membrane prepared in Examples 1-3 has the best sealing performance. This is because, firstly, the composite membrane prepared in Examples 1-3 utilizes the outer layer of nano-SiO2 to fill the gaps between molecules and the middle layer of high-temperature ceramicization to form a sub-nanometer barrier, thus blocking permeation through physical means; secondly, the composite membrane utilizes chemical cross-linking to eliminate interfacial gaps, significantly reducing the permeation channels; and thirdly, the composite membrane utilizes the PE-g-MAH and graphene layers of the inner sealing layer to further improve the sealing performance, and uses fluorocarbon surface treatment to block adsorption permeation on the surface of the composite membrane. In contrast, Comparative Example 1 exhibited poor barrier performance due to interfacial delamination and microcracks, allowing flames to penetrate along the cracks during combustion. In Comparative Example 2, the brominated flame retardant had weak bonding with the PP matrix, leading to easy phase separation. Furthermore, during processing and cooling, the flame retardant crystals and polymer exhibited different shrinkage rates, generating internal stress at the interface and forming micropores, resulting in poor barrier performance. Comparative Example 3, on the other hand, suffered from decreased barrier performance because the surface of the composite film, which had not undergone fluorocarbon treatment, was hydrophilic.
[0073] The peel strength test results are shown in Table 3. Table 3. Peeling data of flame-retardant composite films prepared in Examples 1-3 and Comparative Examples 1-3 As can be seen, the peel strength of Example 1 (18.2 N / cm) is 3 times that of Comparative Example 1 (6.0 N / cm), and after aging (16.4 N / cm), it is 5.5 times that of Comparative Example 1 (3.0 N / cm). This indicates that the transition layer effectively improves the interfacial bonding strength and the durability of the membrane. After the transition layer is set, the epoxy resin undergoes a ring-opening reaction with the PP matrix and the maleic anhydride groups on PE-g-MAH to generate COC ether bonds and ester bonds, forming an epoxy network. At the same time, SiC nanoparticles are embedded in the aforementioned covalently bonded epoxy network to achieve mechanical interlocking. In this way, the inner sealing layer and the intermediate layer form a strong bond, effectively improving the sealing performance and resistance to electrolyte corrosion of the composite membrane. Although Comparative Example 3 has a chemical cross-linking layer, due to the lack of fluorocarbon hydrophobic treatment, water molecules invade the epoxy network, causing partial hydrolysis of the ester bonds. This significantly reduces the interfacial bonding strength of the membrane during aging, with a retention rate of only 80%.
[0074] In summary, this application provides a high-sealing flame-retardant composite film and its preparation method. The outer layer's flame-retardant efficiency and surface density are improved by combining phosphorus-nitrogen synergistic flame-retardant PET with nano-silica. A synergistic flame-retardant intermediate layer is formed by loading modified aluminum hydroxide and zinc borate onto polypropylene as the matrix. An inner sealing layer is formed by blending ethylene-vinyl acetate copolymer with maleic anhydride-grafted polyethylene. Furthermore, this application further enhances flame-retardant and sealing performance by incorporating a transition layer composed of epoxy resin and nano-silicon carbide between the intermediate layer and the inner sealing layer, while also improving the interfacial bonding between the materials. This application overcomes the technical barrier of incompatibility between flame retardancy and sealing performance through synergistic innovation in materials, structure, and process, providing a high-safety, long-life packaging solution for new energy vehicle batteries and high-end electronic devices. The high-sealing flame-retardant composite film provided by this application exhibits excellent flame-retardant and sealing performance, with a limiting oxygen index of 39%, a UL-94 rating of V-0, and a water vapor transmission rate of 8.5 g / m³. 2 • Day, oxygen permeability reaches 10±1cm 3 / m 2 ·day.
[0075] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.
Claims
1. A high-sealing flame-retardant composite membrane, characterized in that, The high-sealing flame-retardant composite film comprises an outer layer, an intermediate layer, a transition layer, and an inner sealing layer stacked sequentially. The outer layer material comprises flame-retardant PET and nano-silica; the intermediate layer material comprises a polypropylene matrix, modified aluminum hydroxide, and zinc borate; the transition layer material comprises epoxy resin and nano-silicon carbide; and the inner sealing layer material comprises ethylene-vinyl acetate copolymer and maleic anhydride-grafted polyethylene. The flame-retardant PET also contains 12-20 wt% phosphorus-nitrogen synergistic flame retardant. The outer layer and the intermediate layer are bonded by physical entanglement, and the transition layer and the inner sealing layer are bonded by chemical cross-linking.
2. The high-sealing flame-retardant composite membrane according to claim 1, characterized in that, The thickness of the high-sealing flame-retardant composite film is 180-250 μm.
3. The high-sealing flame-retardant composite membrane according to claim 2, characterized in that, In the high-sealing flame-retardant composite membrane, the outer layer has a thickness of 40-60 μm, the middle layer has a thickness of 70-90 μm, the transition layer has a thickness of 5-10 μm, and the inner sealing layer has a thickness of 50-90 μm.
4. The high-sealing flame-retardant composite membrane according to claim 1, characterized in that, The mass percentage of nano-silica in the outer layer material is 3-5 wt%; the mass percentage of modified aluminum hydroxide and zinc borate in the intermediate layer material is 25-35 wt%. In the transition layer, the mass ratio of epoxy resin to nano-silicon carbide is (9-11):1; in the inner sealing layer, the mass ratio of ethylene-vinyl acetate copolymer to maleic anhydride grafted polyethylene is 80:(15-25).
5. The high-sealing flame-retardant composite membrane according to claim 4, characterized in that, The mass ratio of modified aluminum hydroxide to zinc borate is (15-25):
10.
6. The high-sealing flame-retardant composite membrane according to claim 1, characterized in that, Ethylene-vinyl acetate copolymers contain 25-30% vinyl acetate.
7. The high-sealing flame-retardant composite membrane according to claim 1, characterized in that, The inner sealing layer material also contains 0.01-10 wt% graphene.
8. A method for preparing a high-sealing flame-retardant composite film according to any one of claims 1-7, characterized in that, Includes the following steps: S1, Flame-retardant PET granules are mixed with nano-silica and melt-granulated to obtain an outer layer material; polypropylene matrix is mixed with modified aluminum hydroxide and zinc borate and melt-granulated to obtain an intermediate layer material; then, the outer layer material and the intermediate layer material are melted separately and extruded together, and after cooling, a first composite film is obtained in which the intermediate layer is closely attached to the outer layer and the thickness of the intermediate layer is greater than the thickness of the outer layer. S2, epoxy resin and nano silicon carbide are uniformly mixed, diluted with acetone and ultrasonically dispersed to obtain a uniform spraying liquid. Then, the spraying liquid is uniformly sprayed onto the surface of the intermediate layer of the first composite film prepared in step S1, and left to stand for the solvent to evaporate naturally to obtain a second composite film containing a transition layer. S3, after mixing and melting ethylene-vinyl acetate copolymer with maleic anhydride grafted polyethylene, the mixture is extruded and coated onto the transition layer surface of the second composite film prepared in step S2, and then hot-pressed to obtain a third composite film containing an inner sealing layer. S4. The third composite film prepared in step S3 is subjected to fluorocarbon plasma surface treatment. Then, the treated composite film roll is transferred to a constant temperature drying room for static curing. Finally, it is rolled up to obtain a high-sealing flame-retardant composite film.
9. The method for preparing the high-sealing flame-retardant composite film according to claim 8, characterized in that, In step S1, the melt granulation process of the outer layer material is as follows: first, flame-retardant PET granules are premixed with nano-silica, then melt-granulated at 240-250℃ using a twin-screw extruder, and finally dried. In step S1, the melt granulation process of the intermediate layer material is as follows: first, polypropylene matrix is premixed with modified aluminum hydroxide and zinc borate, then melt-granulated at 220-230℃ using a twin-screw extruder, and finally dried. The co-extrusion in step S1 specifically refers to the simultaneous extrusion of the outer layer material and the intermediate layer material through a co-extrusion die, followed by rapid shaping using cooling rollers. In step S2, the solid content in the spraying liquid is 15-25%, and the spraying amount is set to 4-8 g / m³. 2 In step S3, the melting temperature of the ethylene-vinyl acetate copolymer and maleic anhydride-grafted polyethylene is 170-180℃; in step S3, a two-roller hot press is used for hot pressing, wherein the upper roller temperature is set to 160-165℃, the lower roller temperature is set to 150-155℃, the pressure is set to 15-20MPa, and the hot pressing time is 20-40s; in step S4, the fluorocarbon plasma surface treatment specifically involves using an atmospheric pressure plasma treatment device to treat the outer surface of the third composite film in a mixed atmosphere of hexafluoropropylene and argon, and the treatment time is 30-40s; in step S4, the temperature of the constant temperature drying oven is 35-45℃, and the static curing time is 24-30h.
10. The method for preparing the high-sealing flame-retardant composite film according to claim 9, characterized in that, In the mixed atmosphere of hexafluoropropylene and argon, the volume ratio of hexafluoropropylene to argon is 1:5.
Citation Information
Patent Citations
Composite film with multiple layers of flame-retardant spaces as well as preparation and application of composite film
CN116674238A
Preparation method of phenolic acid-based phosphorus-nitrogen flame retardant, phenolic acid-based phosphorus-nitrogen flame retardant and application of phenolic acid-based phosphorus-nitrogen flame retardant
CN119874779A
Cited By
Multi-layer co-extrusion polypropylene composite film for capacitor and preparation method of multi-layer co-extrusion polypropylene composite film
CN122008665A
A multilayer co-extruded polypropylene composite film for capacitors and its preparation method
CN122008665B